PENGARUH KOMPETENSI AUDITOR, TEKANAN WAKTU, BEBAN KERJA, DAN PENGALAMAN AUDIT TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN - Naibaho, Jessica Gratia; Astuti, Christina Dwi (Ensiklopedia Sosial Review, 2025)
Abstract: The purpose of this research is to determine the effect of auditor competence, time pressure, workload, and auditor experience on the auditor's ability to detect fraud. The population in this research are junior auditors at Public Accounting Firms (KAP) in Jakarta. The type of data used in this study is quantitative data. The sampling technique used convenience sampling with a sample of 138 respondents. The analysis method used in this study is multiple linear regression. The results of the analysis show that the variables of auditor competence and time pressure do not affect the auditor's ability to detect fraud, while workload and auditor experience has a positive effect on the auditor's ability to detect fraud.Keyword : Auditor Competence;Time Pressure;Workload;Aditor Experience;Auditor’s Ability to Detect Fraud